2019
DOI: 10.1111/tpj.14166
|View full text |Cite
|
Sign up to set email alerts
|

Increased temperatures may safeguard the nutritional quality of crops under future elevated CO2 concentrations

Abstract: SummaryIron (Fe) and zinc (Zn) deficiencies are a global human health problem that may worsen by the growth of crops at elevated atmospheric CO 2 concentration (eCO 2). However, climate change will also involve higher temperature, but it is unclear how the combined effect of eCO 2 and higher temperature will affect the nutritional quality of food crops. To begin to address this question, we grew soybean (Glycine max) in a Temperature by Free‐Air CO 2 Enrichment (T‐FACE) experiment in 2014 and 2015 under ambien… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
39
1

Year Published

2019
2019
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 45 publications
(47 citation statements)
references
References 50 publications
2
39
1
Order By: Relevance
“…However, increasing temperature to 35°C or higher, exceeded the beneficial effects of eCO 2 (Madan et al 2012). The combination of eCO2 with eT has a variable effect on growth and photosynthesis, and is dependent on the range of temperature increase, but in general eCO 2 reduced the negative impact of eT (Köhler et al 2018;Qiao et al 2019;Yu et al 2012). This was confirmed in soybean and maize over five-year growing seasons in open top chambers (Qiao et al 2019).…”
Section: The Effects Of Other Climate Change Factors On Nutrient Accumentioning
confidence: 77%
See 1 more Smart Citation
“…However, increasing temperature to 35°C or higher, exceeded the beneficial effects of eCO 2 (Madan et al 2012). The combination of eCO2 with eT has a variable effect on growth and photosynthesis, and is dependent on the range of temperature increase, but in general eCO 2 reduced the negative impact of eT (Köhler et al 2018;Qiao et al 2019;Yu et al 2012). This was confirmed in soybean and maize over five-year growing seasons in open top chambers (Qiao et al 2019).…”
Section: The Effects Of Other Climate Change Factors On Nutrient Accumentioning
confidence: 77%
“…Sublett et al (2018) studied the consequence of eT (+8°C) on lettuce in a greenhouse experiment, and found a decrease in leaf Mg, K, Ca Mn and Mo concentrations. When looking at temperature and eCO 2 , it was shown that the combination of both factors may restore soybean (Köhler et al 2018) and wheat (Asif et al 2019) seed Fe and Zn concentrations to levels obtained under ambient CO 2 (aCO 2 ). However, since there is a strong species and cultivar dependency on these responses, care must be taken to look at these aspects in detail.…”
Section: The Effects Of Other Climate Change Factors On Nutrient Accumentioning
confidence: 99%
“…enables nesting of open-air drought, temperature, and ozone treatments, as well as the free movement of pests and pathogens, and testing of a range of crop genotypes (e.g., Bourgault et al, 2016Bourgault et al, , 2017Gray et al, 2016;Hasegawa et al, 2013;He et al, 2014;Köhler et al, 2019;Ruiz-Vera et al, 2013).…”
Section: Ainsworth and Longmentioning
confidence: 99%
“…Zhu et al (2018) suggested that many more genotypes would need to be screened in order to identify sufficient genetic variation for selection. To add to this challenge, the presence of other stresses associated with climate change alter grain quality responses to elevated [CO 2 ] (Köhler et al, 2019). Again, this speaks to the need for FACE facilities of adequate scale for breeder selection (Ainsworth et al, 2008).…”
Section: Exploitation Of Genetic Variability Within Crop Germplasmmentioning
confidence: 99%
“…While many studies have shown a reduction in mineral nutrition in crops grown at elevated [CO 2 ], recent studies that investigated the combination of rising [CO 2 ] and warming reported that elevated temperatures can restore mineral concentrations to ambient conditions in soybean (Köhler et al . ; Palacios et al . ).…”
Section: Response Of Plant Productivity To Future [Co2] and [O3]mentioning
confidence: 99%